Genetic patterns related to von Willebrand factor: implications on the need for mechanical ventilation, severity, and death in COVID-19 - López Castro, José; Diz-de Almeida, Silvia; López Reboiro, Manuel L.; Sardiña González, Cristina; Riancho, Jose A.; Rojas-Martinez, Augusto; Lapunzina, Pablo; Flores, Carlos; Cruz, Raquel; Carracedo, Angel (Frontiers in Medicine, 2026)
BackgroundElevated levels of Von Willebrand Factor (VWF) have been associated to an increased need of mechanical ventilation and higher mortality risk in COVID-19 patients, but the hypothesis of a shared genetic background has not been explored.MethodsCommon and low-frequency genetic variants belonging to the VWF, FVIII, and ADAMTS13 genes were tested for association with clinical variables related to severe COVID-19 disease in 9,371 European and 3,495 Latin-American patients. Gene–environment and gene–gene interactions were also explored.ResultsA variant in the VWF gene was associated to the need of invasive mechanical ventilation (IMV) in the Latin-American population. Gene–gene interaction models pointed to an interaction between ADAMTS13 and VWF genes.ConclusionAlthough we did not find significant associations among Europeans, we identified a low-frequency variant belonging to the VWF gene associated with the need of IMV in Latin-Americans.